2017
DOI: 10.1155/2017/4239268
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Community-Acquired Pneumonia: Are All Countries Treating Children in the Same Way? A Literature Review

Abstract: Background Pneumonia represents an important threat to children's health in both developed and developing countries. In the last 10 years, many national and international guidelines on the treatment of pediatric CAP have been published, in order to optimize the prescription of antibiotics and limit their cost and side effects. However, the practical implementation of these guidelines is still limited. Main Text We analyzed the current recommendations for the therapy of pediatric community-acquired pneumonia (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
(90 reference statements)
0
8
0
1
Order By: Relevance
“…These similarities in the findings could be due to the availability of these drugs in these various hospitals and hence their use. Additionally, there could also be some similarities in the treatment guidelines developed by these hospitals in the various hospitals that were considered for the studies [9]. However, the findings of this study were contradicted by what was found in other studies which found that cephalosporins were the most commonly used antibiotics unlike penicillins [21,38].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These similarities in the findings could be due to the availability of these drugs in these various hospitals and hence their use. Additionally, there could also be some similarities in the treatment guidelines developed by these hospitals in the various hospitals that were considered for the studies [9]. However, the findings of this study were contradicted by what was found in other studies which found that cephalosporins were the most commonly used antibiotics unlike penicillins [21,38].…”
Section: Discussionmentioning
confidence: 52%
“…An increase in infections caused by resistant bacteria has called for rational and appropriate use of antibiotics in paediatrics [9]. Antibiotics should be used rightly and for the right patient, at the right time, in the right dose, and administered correctly while providing them at an affordable cost with the right information [10].…”
Section: Introductionmentioning
confidence: 99%
“…Выбор азитромицина является бесспорным врачебным действием при лечении внебольничных пневмоний, вызванных внутриклеточными бактериальными инфектами Chlamydophila pneumoniae, Mycoplasma pneumoniaе, или в случаях отсутствия эффекта от предшествующей терапии β-лактамными антибактериальными средствами [17] Апоптоз Нейтрофилы Индукция апоптоза [51] NK-клетки Индукция апоптоза [36] Фагоцитоз Макрофаги Усиление фагоцитоза (особенно апоптотических нейтрофилов) [23] лином/клавуланатом по уровню клинической эффективности. Также показано, что эффективность комбинированного антибактериального лечения внебольничной пневмонии у детей β-лактамными препаратами с макролидами (азитромицином, эритромицином или кларитромицином) превосходит наблюдаемую при монотерапии β-лактамными антибактериальными средствами [10].…”
Section: клиническая эффективность азитромицина при лечении инфекционunclassified
“…Pneumonia is the leading cause of mortality in children under the age of five throughout the world, with an estimated 1.30 million deaths in 2011, which the majority happened in developing countries (Donà, Luise, Dalt, & Giaquinto, 2017). Pneumonia is inflammation of the lungs caused by pneumococcus, staphylococcus, and streptococcus bacteria.…”
Section: Introductionmentioning
confidence: 99%